Identification of Technical Characteristics of Ergonomic Baby Dining Chair Products - Fithri, Prima; Syafruddin Indrapriyatna, Ahmad; Syaddad Hamdan , Farrell; Handayani Gusmira , Yuni (Andalasian International Journal of Applied Science, Engineering and Technology, 2025)
This research aims to design an ergonomic toddler dining chair that meets the needs of safety, comfort, and usability for families, restaurants, and daycare centers in Padang City. The study identifies deficiencies in existing products and proposes solutions that suit user preferences and ergonomic standards. This research utilizes a mixed-method approach, starting with the Kano model to classify user needs into categories such as "must-have," "performance," and "attractive" features. These needs are then translated into technical specifications using the Quality Function Deployment (QFD) methodology. Data were gathered through questionnaires distributed to families with toddlers and toddler chair providers. The analysis involved validity and reliability tests using SPSS, ensuring the responses were consistent and accurate. The House of Quality (HoQ) matrix was employed in two phases to map customer needs to technical and design characteristics. Anthropometric data were incorporated to ensure that the design meets ergonomic requirements. This research contributes to the theory of ergonomic product development by demonstrating the integrated use of the Canoe and QFD models to prioritize and address user needs effectively. This research offers a solid foundation for developing an ergonomic toddler feeding chair that improves safety and comfort for toddlers, reduces the risk of musculoskeletal disorders, and improves usability for parents and service providers. The findings also emphasize the importance of anthropometric data in creating products tailored to specific user groups. The research made a new contribution to toddler furniture design by developing a dining chair that integrates important ergonomic features, including adjustable height, folding mechanism for portability, secure and comfortable backrest, and durable and easy-to-clean materials. This design addresses the concerns of users identified through comprehensive data analysis, offering a safer and more convenient product compared to the options on the market. In addition, this research framework can be a reference for future studies in developing ergonomic products.